Bolivia: A Gasified Democracy - Assies, Willem (European Review of Latin American and Caribbean Studies, 2004)
In October 2003 a wave of popular protest brought down the Sánchez de Lozada government in Bolivia. The intention to export natural gas to the United States and Mexico triggered the protests, but actually stood for widespread discontent with the Sánchez de Lozada government, the preceding governments and the economic policies pursued since 1985. The events belie the opinion of various students of the Latin American democratic transitions who held that Bolivian democracy was on its way towards consolidation and suggest that the recent inquiries into the quality of Latin American democracies may point a way ahead in rethinking democracy in the region. Taking such assessments as a reference, this article reviews the ‘gas war’ and looks at the Bolivian political regime as it has functioned over the past decades. It will be argued that the ‘pacted democracy’, that until now sustained institutionality, and the economic model adopted in 1985 have excluded an important part of the population, both in political terms and where poverty alleviation and equity is concerned. Increasing popular protest has been met with increasing repression, which gradually turned Bolivia into a ‘democradura’, or a ‘gasified democracy’ that relies on teargas and bullets to uphold itself. At present the country finds itself at a crossroads. It either may reinvent democracy or become an institutionalized ‘democradura’. Resumen: Bolivia: una democracia gasificadaEn octubre de 2003 una ola de protesta popular llevó a la caída del gobierno de Sánchez de Lozada en Bolivia. La intención de exportar gas natural a los Estados Unidos y México gatilló dichas protestas, aunque en realidad reflejaron un descontento general con el gobierno Sánchez de Lozada, los gobiernos anteriores y las políticas económicas implementadas desde 1985. Los sucesos desmienten la opinión de varios analistas de las transiciones democráticas latinoamericanas que afirmaban que la democracia boliviana estaba en camino hacia la consolidación y sugieren que las investigaciones recientes acerca de la calidad de la democracia en América Latina señalan nuevas pautas para repensar la democracia en la región. Tomando tales evaluaciones como punto de referencia este artículo describe la ‘guerra del gas’ y examina la forma de funcionar de la democracia boliviana durante las últimas décadas. Se argumentará que la ‘democracia pactada’, que durante este período aseguró la institucionalidad, y el modelo económico adoptado en 1985, excluyeron a importantes sectores de la población, tanto en términos políticos cómo en lo que se refiere al alivio de la pobreza y la equidad. Protestas crecientes fueron reprimidas con una violencia igualmente creciente, lo que paulatinamente convirtió a Bolivia en una ‘democradura’ o una ‘democracia gasificada’ – que necesita de gas lacrimógeno y balas para sustentarse. De momento, el país se encuentra en un cruce de caminos; o se reinventa la democracia o se institucionaliza la ‘democradura’.